Two new species of Acrocephalomyia Ibáñez-Bernal & Hernández-Ortiz, 2012 from Brazil (Diptera: Ropalomeridae) and a key to known species - Alvim, Edgar; Ale-Rocha, Rosaly (Zootaxa, 2016)
Two new species of Acrocephalomyia Ibáñez-Bernal & Hernández-Ortiz (Diptera, Ropalomeridae) are described. The genus currently includes three species, the type species from Costa Rica, Acrocephalomyia zumbadoi Ibáñez-Bernal & Hernández-Ortiz, and two new species from Brazil herein described, A. torulosa sp. nov., (State of Mato Grosso do Sul, Midwest) and A. pulchra sp. nov. (State of Amazonas, North). A key for the known species of Acrocephalomyia is given and characters of the male terminalia are described and discussed for the first time, with special attention to the "epiphallus”.